A systematic review on the effectiveness of Zingiber officinale in reducing dental caries - Dhanapal, Raghu; Parasuraman, Subramani; Islam Nizami, Mohammed Zahedul; Lin, Galvin Sim Siang; Krithikadatta, Jogikalmat (KeAi Communications Co., 2024)
According to the Global Burden of Disease Study and the World Health Organization, dental caries is one of the most prevalent oral diseases globally. It is well known that dental caries are associated with cariogenic bacteria and their bioflm. Many preventive strategies and therapeutic compounds have been proposed for decades. Among them, various plant based phytochemical compounds have been investigated against cariogenic bacteria. In this review, we plan to show the effectiveness of Zingiber officinale to reduce dental caries. Z. officinale in ginger is a bioactive spice compound that shows antimicrobial activity. Therefore, it is reasonable to consider the antimicrobials and bio lm inhibition properties of bioactive Z. officinale to rationalize its potential in reducing dental caries. While the literature highlights the general antimicrobial properties of Z. officinale, this review focuses on Z. officinale’s capability against cariogenic microbes and their bioflms. Reported results of minimum inhibition concentration (MIC), minimum bactericidal concentration (MBC), and bio lm inhibition (glucans and adhesion) were systematically reviewed. Common search engines like PubMed, Science Direct, and the Web of Science database are used to retrieve data using the keywords“Zingiber officinale” and“dental caries”. Out of 122 resulting reports, 11 of them were included in this review. It can be concluded that Z. officinale effect against cariogenic bacteria varies depending on microbial and analytical factors. However, translational advanced studies have not yet been conducted to verify its clinical application.